Value of Galectin-3 assay in children with heart failure secondary to congenital heart diseases: a prospective study - Nagwan Saleh; Ahmed Khattab; Mohamed Rizk; Sherif Salem; Hany Abo-Haded (BMC, 2020)
Abstract Background Galectin-3 is a new biomarker, which plays an important role in tissue inflammation, cardiac remodeling, and fibrosis. It can be readily measured in the circulation to detect early heart failure (HF). This study aimed to assess the value of galectin-3 assay in early diagnosis of children with heart failure secondary to congenital heart disease (CHD) and correlate it with the patients' outcome. Methods This prospective cohort study included 75 children diagnosed to have CHD; {Group A: 45 CHD children with HF symptoms and reduced ejection fraction (REF) and Group B: 30 CHD children with no HF symptoms and normal ejection fraction (NEF)}. They were compared to 40 age- and sex-matched controls (Group C). Children with CHD undergone history taking, Ross HF classification, Echocardiographic assessment and laboratory investigations including serum galactin-3 level. Results Galectin-3 serum level increased in CHD children, and it showed significant increase in (Gp A) compared to Gp B or Gp C (p = ≤ 0.001). In addition, serum level of Galactin-3 was correlated positively with Ross classification (r = 0.68, p = 0.018) and negatively correlated to EF% (r= -0.61, p ≤ 0.001). Galactin-3 showed better diagnostic value than Ross HF classification in early diagnosis of HF in CHD children with a cut point (≥ 10.4), significantly had 96.7% sensitivity, 90% specificity, 91% positive predictive value, 93.2% negative predictive value, with area under the curve (AUC = 0.96) and 93% accuracy. While there was a significant correlation between Ross HF classification and HF outcome in (Gp A) children (p = 0.05), we did not find any significant correlation between serum galectin-3 level and HF mortality in same group (p = 0.08). Conclusions Galectin-3 assay is a promising marker for early diagnosis of HF in children with CHD; but it has no role in detecting HF mortality.